Decretação ex officio nos contratos relacionais de consumo: o estudo da Norma de Ordem Pública do CDC - Silva, Marcus Vinicius Fernandes Andrade da (2013)
From something seen as clear-cut and uncontroversial this doctoral thesis intends to scrutinize in-depth the viability of the Judge s ex officio, ie, without the need of previous provocation by any of the litigants (ex officio), of the unfair terms in consumer-related contracts, and as corollary of such a possibility, of what was intended by the legislator of Consumer Protection Law when qualifying such a rule as a public one. The controversy was underestimated by this candidate. This underestimation has never been caused by disrespect or contemptuous treatment of the legal controversy, on the contrary. The challenges and difficulties arisen as something thought not possess such profound implications, not only within the material law, but also in procedural law (feared), only made the study and the search for answers more enticing. The Judge s expression in itself (ex officio) about the material law turned itself to certain immanentism of the material law with procedural law. So, as researcher of the Consumer Protection Law, it arises impacts or not on the Judge s expression of an unfair terms or any other contra legem interpretation it is not as simple as it might seem. Modulations, forces and various decisional effects had to be addressed in the search for a better answer. Variation which is amplified both on individual as well as on class actions. In parallel with such a confrontation (discovery), also came the complicating element of demystifying what would be the definition of public order. In Brazilian law, the rule is to perceive public order as something imperative, law binding, unattainable. Those features do not cover encompass all situations of the Brazilian Consumer Law (CDC) and forced the researcher to seek more details in foreign sources. The search for definitions, characteristics and effects in foreign law systems widened up even more what the research sought to analyze. Nevertheless the research s scope, it was realized the confrontation of the features of public order would of use to Brazilian law in itself as the focus on different foreign systems would aggrandize and justify the option for the CDC. Finally, as during this investigation the Superior Court of Justice (STJ) pronouncement number nº. 381, whose content goes against this thesis, came to light, its analysis and confrontation turned out to be inevitable